Cover Feature: Solid State Supercapacitor Based on Manganese Oxide@Reduced Graphene Oxide and Polypyrrole Electrodes (ChemElectroChem 19/2018). Issue 19 (30th August 2018) - Arul, N. Sabari; Han, Jeong In; Chen, Pao Chi
Abstract : The Cover Feature uses words to describe the latest solid‐state supercapacitor research. Manganese oxide @ reduced graphene oxide nanocomposite and polypyrrole are prepared as superior electrode materials for solid‐state supercapacitors. The assembled asymmetric supercapacitor delivers high energy and power density and excellent cycling. All aspects of this research are expressed literarily in this design created by Dr. Mathias Wiechen, Assistant Editor of ChemElectroChem . More information can be found in the Article by N. S. Arul et al. onpage 2747 in Issue 19, 2018 (DOI:10.1002/celc.201800700 ).